Risk factor profile of coronary artery disease in black South Africans - Pieters, Marlien; Dolman, Robin; Ntyintyane, Lucas; Jerling, Johann; Raal, Frederick (SA Heart Journal, 2017)
Objectives: The aim of this study was to investigate the risk factor profile of coronary artery disease (CAD) in black South Africans. The study was motivated by the increased prevalence of CAD in South Africa, probably as a result of urbanisation. Despite this increase, however, very little is known regarding the cause, risk factor profile and clinical presentations of CAD in the black South African population. Design: A case control study was performed investigating 40 (33 men, 7 women) angiographically defined CAD patients and 20 (13 men and 7 women) age and body composition matched controls. Results: There was no difference in physical activity, sociodemographic factors or dietary intakes between the CAD and control group, except for the CAD patients consuming less vit C (40.9 vs 61.3 mg). The CAD group had significantly higher LDL-C, fasting glucose and CRP. There was also a significantly higher prevalence of smokers (35 vs 10%), hypertension (95 vs 75%) small dense LDL (73 vs 15%) and insulin resistance (M-value of 4.15 vs 12.5 mg/kg/min) in the CAD compared to the control group. In a logistic regression model, small dense LDL and insulin resistance were the main predictors of CAD. Conclusions: Black South African CAD patients had increased levels of the same risk factors that are typically seen in Caucasians with insulin resistance and small dense LDL being particularly significant in their contribution.